Documentação pedagógica como artefato formativo: uma narrativa da prática na educação infantil - Moraes, Isabella (2023)
This master's thesis, based on narrative methodology, located in a qualitative paradigm, has as its theme the pedagogical documentation that constitutes a democratic way of working and is inspired by the approach of Reggio Emilia. With practical and theoretical repertoire, based on references such as Mello, Barbosa and Faria, Rinaldi and Dahlberg, pedagogical documentation was defined as a practice that narrates and makes visible the daily lives of children and early childhood educators, with the possibility of legitimizing educational activities, creating space for participation and a source of training and reflection; as well as the other two key concepts of empowerment and democracy, supported by Freire and Moss. Still, this research comprises explanations about experience and listening related to the theme. The research of the theoretical body of this text follows a path that emerged according to the needs that emerged throughout its construction process. The initial idea of this investigation is based on practice, from a formative encounter with a text, which echoed for a while until the time came to give life to the research that aims to understand how the practice of pedagogical documentation generates empowerment process in the training of a childhood educator, guided by the following question of How does the practice of pedagogical generates empowerment process in the training of a childhood educator? This investigative intention is born through the feeling and complexity that emerge when working with/through the artifact of pedagogical documentation, so the relationship with empowerment, which is proposed, becomes relevant and new from the perspective of showing this form of work which is the pedagogical documentation. With this, the research created a possibility of revisiting and studying the past through the research data, which are the pedagogical documentation made by the researcher in the years 2019 and 2020, which had a formative role in bringing to light the complexity of working as an educator in Childhood Education.